Association between peak height velocity (PHV), speed, and agility in pencak silat athletes - Sari, Fenny Novita; Sumartiningsih, Sri (Journal Sport Area, 2025)
Background: Peak height velocity (PHV) is a key indicator of biological maturity in youth athletes, strongly influencing neuromuscular development and physical performance. While PHV has been widely studied in sports science, its association with speed and agility in pencak silat—an Indonesian martial art that relies heavily on explosive movements and motor coordination—remains underexplored. Research Objectives: This study aimed to examine the association between PHV, speed, and agility in young pencak silat athletes and to discuss implications for maturity-based training programs. Methods: A cross-sectional study was conducted on 53 athletes (21 males, 32 females; aged 11–15 years) from the Al Ghozaliyah Pencak Silat Training Center. PHV was estimated using the Mirwald equation from anthropometric measurements. Speed was assessed via a 20 m sprint test, and agility using the Illinois Agility Test. Pearson correlation and independent t-tests were performed to analyze associations and sex-based differences. Finding/Results: PHV showed a significant negative correlation with agility (r = –0.356, p = 0.009) and sprint speed (r = –0.341, p = 0.013), indicating that athletes past PHV performed better. A strong positive correlation was also found between agility and speed (r = 0.509, p < 0.001). Male athletes demonstrated superior sprint performance (p = 0.021), while females recorded slower agility times (p = 0.018). Conclusion: Biological maturity, as reflected by PHV, plays a significant role in shaping speed and agility in young pencak silat athletes. Training programs should therefore be individualized based on maturation status rather than chronological age, with emphasis on neuromuscular development during and after PHV to maximize performance potential and reduce injury risk. Future research should employ longitudinal designs with larger, multi-center samples and explore PHV’s influence on technical–tactical performance and the potential role of bio-banding in martial arts competitions.